(untitled) (FEATURES AND PROBLEMS OF IMPLEMENTING ECONOMIC REFORMS IN AZERBAIJAN, 2025)
The article is devoted to studying the role of Artificial Intelligence (AI) in knowledge management (KM) processes and its legal and institutional significance for Azerbaijan’s economic development. The research analyzes the impact of generative AI, particularly large language models (LLMs), on the creation, storage, and application of knowledge. It is emphasized that these technologies not only accelerate information processing but also introduce new approaches to the formation and utilization of knowledge in public administration and business. In the national context, the emerging legal and institutional framework provides the foundation for digital transformation and the effective use of AI. The scientific novelty of the study lies in the first comprehensive analysis of AI-driven knowledge management in Azerbaijan, with a focus on strengthening economic independence and security. Key challenges are addressed, including algorithmic bias, cybersecurity risks, dependence on foreign technologies, and a shortage of qualified personnel. Strategies for minimizing these risks are proposed, such as developing local language models and national data centers, implementing educational programs, and establishing ethical AI standards. The practical significance of the article is reflected in recommendations for government institutions and businesses on creating a national knowledge base, improving the quality of public services, and accelerating business processes. Furthermore, the importance of human capital development is underlined, since training specialists in knowledge engineering and AI auditing is a prerequisite for long-term sustainability. In the long run, the integration of AI and KM is considered a strategic factor for economic diversification, strengthening technological sovereignty, and enhancing Azerbaijan’s global competitiveness.